2010
DOI: 10.1104/pp.110.162552
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Development Modulates Gene Expression and Metabolite Levels with Possible Feedback Inhibition of Artemisinin in Artemisia annua        

Abstract: The relationship between the transition to budding and flowering in Artemisia annua and the production of the antimalarial sesquiterpene, artemisinin (AN), the dynamics of artemisinic metabolite changes, AN-related transcriptional changes, and plant and trichome developmental changes were measured. Maximum production of AN occurs during full flower stage within floral tissues, but that changes in the leafy bracts and nonbolt leaves as the plant shifts from budding to full flower. Expression levels of early pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 42 publications
5
51
1
Order By: Relevance
“…2 and 3). Several reports have shown that artemisinin has a phytotoxic effect on Artemisia plants and there is a feedback control on artemisinin production (Arsenault et al, 2010a(Arsenault et al, , 2010bZare Mehrjerdi et al, 2013), which could be one of the explanations for the observed down-regulation at 72 and 168 h.…”
Section: Resultsmentioning
confidence: 96%
“…2 and 3). Several reports have shown that artemisinin has a phytotoxic effect on Artemisia plants and there is a feedback control on artemisinin production (Arsenault et al, 2010a(Arsenault et al, , 2010bZare Mehrjerdi et al, 2013), which could be one of the explanations for the observed down-regulation at 72 and 168 h.…”
Section: Resultsmentioning
confidence: 96%
“…When AaWRKY1 was transferred into A. annua, artemisinin biosynthesis was found to be greatly enhanced (Ma et al 2009;Han et al 2014). It was also know that the changes of glandular trichomes are closely correlated with artemisinin levels, and the densities of glandular trichomes are dependent on the developmental stages and organ positions (Arsenault et al 2010).…”
Section: Glandular Trichomes Are Dominant Sites Storing Artemisininmentioning
confidence: 96%
“…Another possibility could also come from a difference of artemisinin content in developing leaves. Because it was observed that the maximum artemisinin production occurs by the fully flowering stage within floral tissues, but it can alters in the leafy bracts and non-bolt leaves when the development of plants shifts from budding to fully flowering (Arsenault et al 2010). Where is artemisinin synthesized and sequestered?…”
Section: When Is Artemisinin Synthesized?mentioning
confidence: 99%
“…CYP71AVI belongs to the cytochrome P450 family. It is a multifunctional sesquiterpene oxidase with a key role in the biosynthesis of sesquiterpene lactone artemisinin which involves the conversion of amorpha-4,11-diene to artemisinic acid [7][8][9][10]. Optimization gene encoding CYP71AVI has been conducted to make its expression more optimum in E. coli.…”
Section: Introductionmentioning
confidence: 99%